Feasibility and reliability of measured glomerular filtration rate with [I125]-iothalamate among young adults with mild-to-moderate cerebral palsy - Whitney, Daniel G.; Oliverio, Andrea L.; Kreschmer, Jodi; Bolde, Shannen; Hurvitz, Edward A.; Wong, Ka Kit (Frontiers in Medicine, 2024)
Objective: Despite the need, measuring glomerular filtration rate (mGFR) is not routinely performed for adults with cerebral palsy (CP), possibly due to unknown feasibility given secondary complications of CP. The objective was to assess the feasibility and reliability of mGFR and explore factors associated with eGFR-mGFR discordance among young adults with mild-to-moderate CP.Methods: This single-center, cross-sectional study recruited 18-40-year-olds with CP gross motor function classification system (GMFCS) I-III. Exclusion was pregnancy/lactation, cognitive impairment, or contraindication to mGFR. A routine clinical protocol for mGFR and eGFR was used. mGFR feasibility was assessed based on the number of participants that completed testing. mGFR reliability was assessed by the coefficient of variation (CV) across the four, 30-minute intervals. The association between age, sex, and GMFCS with percent of eGFR-mGFR discordance was assessed.Results: Of the 19 participants enrolled, 18 completed testing (mean age [SD], 29.9 [7.4] years, n=10 female, n=10/3/5 for GMFCS I/II/III) and most (n=15) and most had an mGFR >90ml/min; 14 participants (77.8%) had a CV<20%, 2 had a CV between 20 and 25%, and 2 had a CV>50%. eGFR overestimated mGFR by a median (interquartile range) of 17.5% (2-38%); the full range of misestimation was -20.5-174.3%. Increasing age and GMFCS levels exhibited notable, but weak-tomodest, associations with a larger eGFR-mGFR discordance.Discussion: Routine mGFR was feasible to obtain with reasonable reliability among this small sample. eGFR overestimated mGFR by a notable amount, which may be associated with patient-level factors.